EVALUATING DISCREPANCIES IN TYPE 2 DIABETES CARE: AN IN-DEPTH ANALYSIS IN THE UNITED STATES - Miller, Robert (Ayden International Journal of Basic and Applied Sciences, 2024)
Type 2 Diabetes Mellitus (T2D) has reached epidemic proportions in the United States, affecting over 30 million Americans, with an additional 34% of the adult population considered prediabetic. The diagnosis of T2D is linked to a significant reduction in life expectancy, with a 10-year decline, and an added direct medical cost of 9,600 per diabetes patient. Poor management of T2D can lead to a range of complications, both microvascular (nephropathy, neuropathy, retinopathy) and macroscopic (heart disease, stroke, peripheral artery disease). The risks associated with inadequately managed T2D are substantial, doubling the likelihood of cardiovascular disease mortality compared to individuals without T2D. To prevent disease progression and reduce the occurrence of diabetes-related complications, intensive and meticulous T2D management is recommended by the American Diabetes Association (ADA) guidelines. The ADA's Standards of Medical Care in Diabetes offers comprehensive guidelines for the effective treatment and management of T2D, with annual updates based on a thorough review of clinical diabetes literature and feedback from the medical community, including the ADA's Professional Practice Committee. The intricacy of proper T2D management is underscored by the ADA's Comprehensive Medical Evaluation, which serves as a blueprint for initial and follow-up diabetes visits. This evaluation comprises 59 distinct care processes categorized into medical history, social history, medications, vaccinations, technology utilization, screenings, laboratory evaluation, physician examination, and treatment planning.